Sex-differences in the risk of carpal tunnel syndrome: results from a large Ontario, Canada worker cohort - Fanni R. Eros; Paul A. Demers; Jeavana Sritharan (BMC Musculoskeletal Disorders)
Abstract Background Carpal tunnel syndrome (CTS) is a prevalent cumulative strain injury associated with occupational risk factors such as vibration, repetitive and forceful wrist movements, and awkward wrist postures. This study aimed to identify Ontario workers at elevated risk for CTS and to explore sex differences in CTS risk among workers. Methods The Occupational Disease Surveillance System (ODSS) links accepted lost time compensation claims to health administrative databases. CTS cases were identified from physician billing (Ontario Health Insurance Plan) records and defined as at least one record for CTS surgery (fee code N290) between 2002 and 2020. A 3-year washout period and restricted follow-up period of 3 years were applied. A total of 792,769 workers were included in the analytical cohort. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI) for CTS by occupation and industry, adjusted for age and birth year, stratified by sex. Results A total of 3,224 CTS cases among females (f) and 2,992 cases among males (m) were identified in the cohort. We observed elevated risks of CTS in many occupations requiring repetitive and forceful manual work: slaughtering and meat cutting, canning, curing and packing (HRf = 2.28, 95%CI = 1.42–3.68; HRm = 1.95, 95%CI = 1.33–2.85); welding and flame cutting (HRf = 1.83, 95%CI = 1.01–3.32; HRm = 1.65, 95%CI = 1.35–2.01); motor vehicle fabricating and assembling (HRf = 2.14, 95%CI = 1.74–2.62; HRm = 2.43, 95%CI = 2.04–2.89); and packaging (HRf = 2.06, 95%CI = 1.43–2.97; HRm = 1.82, 95%CI = 1.12–2.98). Elevated risks were observed among males employed as nursing aides and orderlies (HRm = 1.72, 95%CI = 1.13–2.62), in mining (HRm = 1.57, 95%CI = 1.01–2.45), and in construction (HRm = 1.32, 95%CI = 1.19–1.47). Elevated risks were observed among females in mineral, metal, chemical processing (HRf = 1.58, 95%CI = 1.27–1.97), textile processing (HRf = 1.89, 95%CI = 1.22–2.94), wood machining (HRf = 2.84, 95%CI = 1.47–5.45), and females employed as janitors, charworkers and cleaners (HRf = 1.50, 95%CI = 1.32–1.71). Findings by industry were consistent with occupation results. Conclusion The risk of CTS varied by occupation, industry, and sex in this large cohort. Workers engaged in highly repetitive and forceful manual work were at elevated CTS risk, highlighting the need to further understand and reduce ergonomic hazards among identified groups. Future studies should also explore CTS risk by sex, with a focus on female workers.